2023
DOI: 10.1111/dom.15045
|View full text |Cite
|
Sign up to set email alerts
|

Once‐weekly semaglutide use in patients with type 2 diabetes: Results from the SURE France multicentre, prospective, observational study

Abstract: Aims: Real-world data are required to support glucagon-like peptide-1 receptor agonist use in type 2 diabetes (T2D). SURE France assessed once-weekly semaglutide in adults with T2D in real-world clinical practice. Materials andMethods: This multicentre, prospective, open-label, single-arm study included adults with T2D and ≥1 documented glycated haemoglobin (HbA1c) value ≤12 weeks before semaglutide initiation. The primary endpoint was HbA1c change from baseline to end of study (EOS; $30 weeks). Secondary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
4
5
1
Order By: Relevance
“…This result is also superior to findings in real-world studies in cohorts followed in other settings; for example, 51.7% of the participants in the SURE France study achieved an HbA1c target of <7%. 10 In line with recent real-world studies, a decrease proportion of the semaglutide cohort concomitant glucose-lowering medications from baseline, in contrast, an increase proportion of non-GLP-1RA cohort in our study. 11 This implies that semaglutide may have been used to simplify the treatment regimen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is also superior to findings in real-world studies in cohorts followed in other settings; for example, 51.7% of the participants in the SURE France study achieved an HbA1c target of <7%. 10 In line with recent real-world studies, a decrease proportion of the semaglutide cohort concomitant glucose-lowering medications from baseline, in contrast, an increase proportion of non-GLP-1RA cohort in our study. 11 This implies that semaglutide may have been used to simplify the treatment regimen.…”
Section: Discussionsupporting
confidence: 92%
“…The overall percentage of participants achieving an HbA1c level <7% was slightly higher in our study than in the SUSTAIN 1–5 and 7 studies. This result is also superior to findings in real‐world studies in cohorts followed in other settings; for example, 51.7% of the participants in the SURE France study achieved an HbA1c target of <7% 10 …”
Section: Discussioncontrasting
confidence: 69%
“…The program found that once-weekly administration of 1.0 mg or less of semaglutide resulted in a weight loss effect of 4.3 to 7.8 kg in patients with type 2 diabetes. [26][27][28][29][30][31][32][33][34] Retrospective studies above are similar to the results obtained in our study. In another retrospective study of 1.0 mg or less semaglutide after 2 years of follow-up, patients with diabetes had a weight loss of 9.72 kg.…”
Section: Discussionsupporting
confidence: 90%
“…The glucose control outcomes in COLIBRI are similar to those of other real-world experiences. The SURE investigated OWS in a real-world setting in several European countries [ 9 16 ] and Canada [ 17 ]. The mean change in the SURE studies for HbA1c ranged from − 0.8% to − 1.5%.…”
Section: Discussionmentioning
confidence: 99%